La dilación poética del destierro: El tema de la partida del héroe en el Cantar de Mio Cid - Zubillaga, Carina (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2007)
The topic of the hero's departure in Cantar del Mio Cid acquires a progressive development as a christian proof. The analysis of Rodrigo and Jimena's prayers, at the beginning of the first cantar, allows to distinguish the abeyances of the exile as an expression of a growing trust in the divine intervention as a guide of the heroic deed.